Implications of cross-linguistic correspondence for teaching idioms - Rastegar, Aria (Pedagogical Linguistics, 2025)
This study investigates how cross-linguistic correspondence affects the interpretation of idioms in unfamiliar languages. Using a categorization framework inspired by construction grammar principles, we categorize idioms based on their form-meaning correspondences across Persian and German: those sharing both form and meaning (SI), only formal features (SL), or only meaning components (SM). In an experimental study, 30 adult German L1 speakers chose between figurative, literal, and non-canonical figurative interpretations for literally-translated Persian idioms from these categories alongside German control idioms. The statistical analyses did not find a significant difference between idioms with both formal and semantic correspondence (SI) and the control German idioms. However, our results indicated a significant decline in figurative interpretation rates for idioms that share only formal characteristics (SL) or meaning components (SM). Multinomial analysis revealed that as cross-linguistic correspondence decreased, the judgments of the participants changed from confident figurative interpretations to more distributed response patterns across literal, figurative, and non-canonical figurative interpretations. These findings suggest that the cross-linguistic correspondence in the form and meaning of idioms between the L1 of the participants and an unfamiliar language can facilitate the understanding of idioms. However, partial correspondence may impede understanding by creating misleading guesses about the meaning of idioms, with participants mainly selecting literal interpretations.
CRIS-Team Scopus Importer:2025-11-28
Keywords: construction grammar; cross-linguistic influence in language pedagogy; idiom comprehension; second language acquisition